CD14+ Cells with the Phenotype of Infiltrated Monocytes Consist of Distinct Populations Characterized by Anti-inflammatory as well as Pro-inflammatory Activity in Gouty Arthritis - Jeong, Ji Hye; Hong, Seokchan; Kwon, Oh Chan; Ghang, Byeongzu; Hwang, Inseok; Kim, Yong-Gil; Lee, Chang-Keun; Yoo, Bin (Frontiers in Immunology, 2017)
It has been suggested that inflammasome-mediated IL-1β production in monocytic cells is responsible for the acute inflammatory response in gouty arthritis. However, phenotypical and functional analyses of monocytes during gouty arthritis have yet to be conducted. Therefore, we investigated the characteristics of monocytes/macrophages in the synovial fluid cells of patients with acute gout. The frequency of monocytes/macrophages in the synovial fluid mononuclear cells of patients was examined. The expression of markers for monocyte recruitment and tissue-resident macrophages, and the production of proinflammatory and anti-inflammatory cytokines were analyzed in the monocytes/macrophages of patients with acute gout attacks. The frequency of CD14+CD3−CD19−CD56− monocytes/macrophages was markedly increased in the synovial fluid mononuclear cells of patients with gout compared to those of patients with rheumatoid arthritis (RA). CD14+ cells showed the phenotypes of infiltrated monocytes rather than tissue-resident macrophages, characterized by a high expression of CCR2, MRP8, and MRP14, but a low expression of MERTK and 25F9. These cells had the capacity to produce proinflammatory cytokines such as TNF-α and IL-1β after stimulation with lipopolysaccharides. In addition, anti-inflammatory features, including CD163 expression and IL-10 production from CD14+ cells, were significantly higher in patients with gout than in those with RA. Thus, our results indicate that monocytes/macrophages from patients with gout have the phenotype of infiltrated monocytes, and these cells exhibit anti-inflammatory activities as well as proinflammatory functions. This appears to be a mechanism for the robust but spontaneous resolution of acute inflammation in gout.